Effects of BBF (bubaline biological fluids) on post incubation motility of buffalo spermatozoa* - AGARWAL, RAJNISH; SINGH, L P (The Indian Journal of Animal Sciences, 2013)
Bubahnc biological fluid possesses a variety of biochemicals which might influence the spem1atozoal motility. To assess their effcct 4 biological flUIds i.e. follicular (FF), oViductal (OVF), allantoic (ALF) and anidrotic (AMF) were collected from fresh morbid genitalia, obtained immediately after slaughter from local abattoir, and were used in vaned concentratIOns to study the effect on cauda epIdIdymal spennatozoal motility. Thc result obtained revealed a highest motilIty in J% FF, 50% OVF and 30% ALP. However, in AMF there was severe, ham1ful and deleterious effect on spermatozoa Thus the present investigation resulted m a positive and significant effect on motility of epididymal spermatozoa due to addition of F F, O V F and A L F in the medium.